2020
DOI: 10.1097/md.0000000000020238
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer with invasive micropapillary components (IMPCs) shows high lymph node metastasis and a poor prognosis

Abstract: Objects: The present study aimed to identify the clinicopathological characteristics of colorectal cancer (CRC) with invasive micropapillary components (IMPCs) and the relationship between different amounts of micropapillary components and lymph node metastasis. Methods: A cohort of 363 patients with CRC who underwent surgical treatment in the Second Affiliated Hospital of Zhejiang University School of Medicine between January 2013 and December 2016 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Previous research has reported that the incidence of CRC with MPP is 9.4–27.8% ( 6 , 33 , 34 ), and it was accompanied by aggressive histological features, including higher levels of lymphovascular and perineural invasion, more frequent lymph node and distant metastases and higher TNM stages ( 6 , 18 , 34 , 35 ). The present study, consistent with previous studies ( 3 , 4 , 6 ), identified 19.8% of CRCs with a MPC component (90/453 cases). It was also reported that CRC with MPP was significantly associated with more frequent lymph node metastasis and higher TNM stages.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Previous research has reported that the incidence of CRC with MPP is 9.4–27.8% ( 6 , 33 , 34 ), and it was accompanied by aggressive histological features, including higher levels of lymphovascular and perineural invasion, more frequent lymph node and distant metastases and higher TNM stages ( 6 , 18 , 34 , 35 ). The present study, consistent with previous studies ( 3 , 4 , 6 ), identified 19.8% of CRCs with a MPC component (90/453 cases). It was also reported that CRC with MPP was significantly associated with more frequent lymph node metastasis and higher TNM stages.…”
Section: Discussionsupporting
confidence: 93%
“…I/O pattern (I/OP) staining of EMA/mucin (MUC)1 has also been confirmed in CRC with micropapillary components (4,20,22,23). However, some studies have demonstrated that the sensitivity of EMA/MUC-1 staining is not high, and >50% of cases have no EMA staining (4,(23)(24)(25). Like EMA/MUC-1, villin is a surface-related glycoprotein and is also expressed in the normal colorectal mucosa (26).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations